Effects of decomposers and herbivores on plant performance and aboveground plant-insect interactions - Poveda, Katja; Steffan-Dewenter, Ingolf; Scheu, Stefan; Tscharntke, Teja (Oikos, 2005)
Most ecologists acknowledge that plants are subject to complex interactions between both below- and aboveground dwelling animals. However, these complex interactions are seldomly investigated simultaneously. In a factorial common garden experiment we tested single and combined effects of decomposers, root herbivores and leaf herbivores on the growth, flower visitation, and abundance of naturally colonizing aphids and parasitoids on wild mustard (Sinapis arvensis). We found that the individual presence of either root herbivores or decomposers resulted in increased aphid abundance, demonstrating that the same aboveground plant-insect interaction can be released by different belowground processes. Enhanced aphid densities caused higher numbers of parasitoids. Furthermore, decomposers increased plant growth and plant fitness (measured as the number of seeds produced), indicating that mustard may benefit from nutrients provided by decomposers, regardless whether plants are attacked by root herbivores or leaf herbivores, or both simultaneously. More flower visits were observed in plants attacked by root herbivores but without leaf herbivores than in plants with both herbivores, suggesting that root herbivory can modify flower attractivity to pollinators. Our results suggest that patterns in plant-insect interactions above the ground are not only affected by aboveground factors but also by a wealth of different belowground processes mediated by the plant.